Kuyper and vaccinations: a case study in Kuyper’s approach to an ethical issue - Bishop, Steven (Koers, 2019)
The 2019 translation of the second volume of Abraham Kuyper’s Pro Rege contains chapters on his approach to vaccinations. This article examines his arguments in favour of vaccinations as a case study on Kuyper’s approach to an ethical issue. Kuyper utilizes both sphere sovereignty and common grace as the key philosophical tools as well as using scriptural, rhetorical and pragmatic arguments to make his case.